Fighting salt or enemies: shared perception and signaling strategies. (December 2021) - Gigli-Bisceglia, Nora; Testerink, Christa
Abstract: Plants react to a myriad of biotic and abiotic environmental signals through specific cellular mechanisms required for survival under stress. Although pathogen perception has been widely studied and characterized, salt stress perception and signaling remain largely elusive. Recent observations, obtained in the model plant Arabidopsis thaliana, show that perception of specific features of pathogens also allows plants to mount salt stress resilience pathways, highlighting the possibility that salt sensing and pathogen perception mechanisms partially overlap. We discuss these overlapping strategies and examine the emerging role of A. thaliana cell wall and plasma membrane components in activating both salt- and pathogen-induced responses, as part of exquisite mechanisms underlying perception of damage and danger. This knowledge helps understanding the complexity of plant responses to pathogens and salinity, leading to new hypotheses that could explain why plants evolved similar strategies to respond to these, at first sight, very different types of stimuli.